Dam pre-release as an important operation strategy in reducing flood impact in Malaysia - Hidayah Ishak, N. (EDP Sciences, 2018)
The 2014 flood was reported to be one of the worst natural disaster has ever affected several states in the northern part of Peninsular Malaysia. Overwhelming rainfall was noted as one of the main factors causing such impact, which was claimed to be unprecedented to some extent. The state of Perak, which is blessed with four cascading dams had also experienced flood damage at a scale that was considered the worst in history. The rainfall received had caused the dam to reach danger level that necessitated additional discharge to be released. Safety of the dams was of great importance and such unavoidable additional discharge was allowed to avoid catastrophic failure of the dam structures. This paper discusses the dam pre-release as a significant dam management strategy in reducing flood impact. An important balance between required dam storage to be maintained and the risk element that can be afforded is the crucial factor in such enhanced operation strategy. While further possibility in developing a carefully engineered dam pre-release strategy can be explored for dam operation in Malaysia, this has already been introduced in some developed countries. Australia and South Africa are examples where pre-release has been practiced and proven to reduce flood risk. The concept involves controlling the dam lake level throughout the year, in reference to the rainfall data and the hydrological properties for the catchment area of the dams. Plentiful data analysis need to be done in contemplation of producing the optimal pre-release model. The amount of heavy rainfalls received is beyond human control but the distribution of the discharge from the dams can be further managed with the appropriate pre-release strategy. Â© The Authors, published by EDP Sciences, 2018.